Development of models and methods of parameters optimization of reliability improving system in 10 kV branched networks - Сиротенко, Михаил Александрович (Technology audit and production reserves, 2015)
Different devices, such as signs of damaged areas, line disconnectors, circuit bus-sectionalizing machines and devices for automatic entry of reserve are used to improve the reliability of power supply to consumers in the 10 kV distribution network. Optimization of means of improving reliability is an urgent task. However, existing calculated methods does not take into account the possibility of installing the network of several types of devices or require to perform a large number of iterations when searching for the optimum scheme of their deployment. To solve this problem it is proposed a mathematical model for evaluate electricity shortage and average time of search fault location to take into account the existence of different means for improving the reliability of the network. The importance of these results lies in the fact that based on the proposed model has been developed computer program that allows automatically searching for the optimal layout of devices in a redundant and non-redundant power lines.